The Influence of ROHUPA Media (Letter Wheel and Reading Board) on Students' Beginning Reading Skills at MIN Kota Medan - Rahma Fadillah Siregar; Riris Nurkholidah Rambe; Auffah Yumni (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
The Effect of Letter Wheel and Reading Board Media on Students' Beginning Reading Skills at MIN Kota Medan is based on students' difficulties in recognizing letters, recognizing letters with the same shape, spelling letters, and combining letters into words which result in students not understanding what they are going to read. This study aims to determine the effect of letter wheel and reading board media in improving the beginning reading skills of first grade students at MIN Kota Medan. This study is a quantitative study with a quasi-experimental design. The research sample consisted of 25 students, who were divided into two groups, namely, the experimental group using letter wheel and reading board media and the control group using conventional media. Data collection was carried out through Pretest and Posttest questions. The data obtained were analyzed using normality tests, homogeneity tests, and hypothesis tests. From the results of the research conducted, it was found that there was a significant influence of letter wheel and reading board media on the beginning reading skills of first grade students at MIN 7 Kota Medan. This is also proven by the results of the hypothesis test where the sig (2-tailed) in the experimental class is 0.000 < 0.05, meaning there is an effect of the treatment in the experimental class. Therefore, Ha is accepted and Ho is rejected at the level of α = 0.05. Thus, it can be concluded that the letter wheel and reading board media have a significant influence in improving the initial reading ability of first-grade students at MIN 7 Medan City